TAURODONTISM – A CHALLENGE FOR PEDIATRIC DENTISTS - Vasilica Toma; Diana Florea; Otilia Humulescu; Livia Bobu; Mihaela Sălceanu; Loredana Golovcencu; Alina Adumitroaie; Veronica Pintiliciuc; Cezara Onică; Carina Balcoș; Daniela Anistoroaei (Romanian Journal of Oral Rehabilitation, 2023)
Aim of the study The purpose of this paper is to review existent literature regarding taurodontism and to highlight the clinical challenges of this pathology in paediatric dentistry. Material and methods Literature was searched for clinical studies and descriptive papers with titles containing the words “taurodontism”, “enlarged pulp chamber”, “bull teeth” “Hertwig epithelial rooth sheath”. Results Taurodontism is a dental developmental disturbanc in which the body is enlarged at the expense of the roots. An enlarged pulp chamber, apical displacement of the pulpal floor and lack of constriction at the cement-enamel junction are the characteristic features. It appears most frequently as an isolated anomaly, but its association with several syndromes and abnormalities has also been reported. Endodontic treatment of taurodontic teeth is stated to be complicated and difficult due to the complexity of the tooth morphology. Conclusions Taurodontic teeth bring a series of challenges to the dental practitioner, from a morphological standpoint, endodontic treatment, periodontal and surgical implications. Literature is scarce regarding protocols for managing teeth with taurodontism, therefore it is in the hand of the clinician to review the best treatment options for those teeth, considering that they are aware of the specific characteristics of the pathology.